Learning Achievement in Physical Education about Basic Movement Exercises the Instructional Management Plan was used as a Habit-forming Process of Primary Student, Prathomsuksa 3 at Anubarnkantharawichai School - Kongpolprom, Nutchanon; Leepromma, Samarnchai; Saramano, Boonyaporn; Saensuwan, Kitichai; Pooksap , Thaweesuk; Sutthisai , Sutthirak (Interdisciplinary Academic and Research Journal, 2023)
Learning management through the process of character building is a learning approach aimed at cultivating the qualities and personality of students. It involves organizing learning activities that align with the developmental levels of behavior traits, leading to the development of positive and enduring character traits in students. The objectives of this research are as follows: (1) Determine the effectiveness of the learning management plan for physical education, focusing on the basic movement patterns, using a character-building learning approach based on the 75/75 standard criteria. (2) Compare the learning outcomes before and after implementing the character-building learning approach for physical education, focusing on the basic movement patterns. And (3) Investigate the satisfaction level of students regarding the character-building learning approach for physical education, focusing on the basic movement patterns. The sample group for this research consists of 42 students from prathomsuksa 3/1, selected through purposive sampling. The research tools utilized in this study include (1) a Learning management plan for physical education using a character-building learning approach. (2) Test measuring learning outcomes. And (3) Questionnaire assessing satisfaction with the learning management approach. The research findings indicate that: (1) The effectiveness of the learning management plan for physical education, employing a character-building learning approach, achieved a score of 86.96/78.65, surpassing the set criteria of 75/75. (2) Students’ learning outcomes after implementing the character-building learning approach were significantly higher than before, with statistical significance at the .05 level. And (3) Overall, students expressed the highest level of satisfaction with the character-building learning approach for physical education.